2023
DOI: 10.3390/v15091918
|View full text |Cite
|
Sign up to set email alerts
|

Placental Infection Associated with SARS-CoV-2 Wildtype Variant and Variants of Concern

Ana Medel-Martinez,
Cristina Paules,
María Peran
et al.

Abstract: The original SARS-CoV-2 lineages have been replaced by successive variants of concern (VOCs) over time. The aim of this study was to perform an assessment of the placental infection by SARS-CoV-2 according to the predominant variant at the moment of COVID-19 diagnosis. This was a prospective study of SARS-CoV-2-positive pregnant women between March 2020 and March 2022. The population was divided into pregnancies affected by COVID-19 disease during 2020 (Pre-VOC group) and pregnancies affected after December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…A previous study correlated placental lesions in pregnant women with COVID-19 with pregnancy outcomes [ 35 ]. Ana Medel-Martinez et al suggested that the frequency of SARS-CoV-2-positive placental tests may differ based on SARS-CoV-2 variants [ 36 ]. However, a prospective case-control study found that SARS-CoV-2 infection during the third trimester did not influence placental histological findings [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study correlated placental lesions in pregnant women with COVID-19 with pregnancy outcomes [ 35 ]. Ana Medel-Martinez et al suggested that the frequency of SARS-CoV-2-positive placental tests may differ based on SARS-CoV-2 variants [ 36 ]. However, a prospective case-control study found that SARS-CoV-2 infection during the third trimester did not influence placental histological findings [ 37 ].…”
Section: Discussionmentioning
confidence: 99%